2018
DOI: 10.6002/ect.2016.0230
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: The identification of variables related to the survival of heart transplant patients is vital for a good medical practice. Few studies have examined this issue in a Latin American population. Therefore, the aim of this study was to analyze, retrospectively, the survival and mortality characteristics of patients after heart transplant. Materials and Methods: Information on patients was obtained through review of medical records; we collected information on all patients who underwent this procedure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…For instance, Booth et al reported that pre-transplant total cholesterol levels >5.5 mmol/L are associated with higher patient survival but show no difference in graft survival [ 25 ]. Another retrospective clinical study demonstrated that lower total cholesterol levels (<160 mg/dL) negatively impact the survival of heart transplant patients at the 5-year mark [ 26 ]. Additionally, Soltanian et al observed that lower LDL cholesterol levels before transplantation can decrease the risk of graft loss after kidney transplantation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Booth et al reported that pre-transplant total cholesterol levels >5.5 mmol/L are associated with higher patient survival but show no difference in graft survival [ 25 ]. Another retrospective clinical study demonstrated that lower total cholesterol levels (<160 mg/dL) negatively impact the survival of heart transplant patients at the 5-year mark [ 26 ]. Additionally, Soltanian et al observed that lower LDL cholesterol levels before transplantation can decrease the risk of graft loss after kidney transplantation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%